Diethylcarbamazine Attenuates the Development of Carrageenan-Induced Lung Injury in Mice - Ribeiro, Edlene Lima; Barbosa, Karla Patricia de Souza; Fragoso, Ingrid Tavares; Donato, Mariana Aragão Matos; Oliveira dos Santos Gomes, Fabiana; Silva, Bruna Santos da; Silva, Amanda Karolina Soares e; Rocha, Sura Wanessa Santos; Amaro da Silva Junior, Valdemiro; Peixoto, Christina Alves (Mediators of Inflammation, 2014)
Diethylcarbamazine (DEC) is an antifilarial drug with potent anti-inflammatory properties as a result of its interference with the metabolism of arachidonic acid. The aim of the present study was to evaluate the anti-inflammatory activity of DEC in a mouse model of acute inflammation (carrageenan-induced pleurisy). The injection of carrageenan into the pleural cavity induced the accumulation of fluid containing a large number of polymorphonuclear cells (PMNs) as well as infiltration of PMNs in lung tissues and increased production of nitrite and tumor necrosis factor-α and increased expression of interleukin-1β, cyclooxygenase (COX-2), and inducible nitric oxide synthase. Carrageenan also induced the expression of nuclear factor-κB. The oral administration of DEC (50 mg/Kg) three days prior to the carrageenan challenge led to a significant reduction in all inflammation markers. The present findings demonstrate that DEC is a potential drug for the treatment of acute lung inflammation.